Contrast-enhanced ultrasound-guided feeding artery ablation as add-on to percutaneous radiofrequency ablation for hypervascular hepatocellular carcinoma with a modified ablative technique and tumor perfusion evaluation. (1st January 2020) - Li, Xiaoju; Xu, Ming; Liu, Ming; Tan, Yang; Zhuang, Bowen; Lin, Manxia; Kuang, Ming; Xie, Xiaoyan
Abstract: Objectives: To establish a modified strategy of the feeding artery ablation (FAA) procedure as an add-on to percutaneous radiofrequency ablation (RFA) for patients with hypervascular hepatocellular carcinoma (HCC), and to evaluate the outcomes. Materials and methods: For this prospective, single-arm study, from June 2014 to August 2016, twenty-five patients with hypervascular HCC, 2–5 cm in diameter were treated by contrast-enhanced ultrasound (CEUS)-guided FAA before conventional RFA. Technical success of FAA and subsequent perfusion change of the tumor were evaluated by CEUS. Technical efficacy and ablation sizes were evaluated by CT/MRI at 1 month. Therapeutic outcomes, including local tumor progression (LTP), overall survival (OS), and recurrence-free survival (RFS) were evaluated using the Kaplan–Meier method. Results: One or two target feeding arteries were visible on CEUS for 52.6% (61/116) of the hypervascular HCCs 2–5 cm in diameter. The technical success rate of the FAA was 100%; 13/25 (52.0%) target tumors were evaluated as complete perfusion response, while 12/25 (48.0%) were evaluated as partial perfusion response. The ablation volume was 41.9 ± 17.5 cm 3 (14.9–78.2 cm 3 ) and the ablative safety margin was 8.2 ± 1.9 mm (4–12 mm) at the 1-month evaluation. These parameters did not differ significantly between the complete and partial subgroups. The cumulative rates of LTP at 1-, 2-, and 3-year follow-ups were 0.0%, 4.2% and 4.2%, respectively. The 3-year OS and RFS were 70.3% vs. 59.8%, respectively. There were no treatment-related deaths. Major complications occurred in one patient (4.0%). Conclusion: As an add-on to conventional percutaneous RFA, tailored CEUS-guided FAA can reduce tumor perfusion and provide good local control of HCC.